Assessment of Health Risks to People in Northeastern Thailand from the Intake of Sodium and Synthetic Preservatives Contained in Traditional Thai Fermented Fish Sauce (Nam-Pla-Ra) and Their Pathogenic Prevalence - Hirunsorn, Pimnibha; Isnainia, Mutiara Nur (Trends in Sciences, 2022)
This research aims to assess the health risks in Thailand from sodium and synthetic preservatives in traditional Thai fermented fish sauce (nam-pla-ra) and their pathogenic prevalence. Of 54 pasteurized-bottles and 37 bottles of Thai Papaya salad (somtum) sold by street vendors, the ingredients containing preservatives were found to be 63 (70 %) comprising 67 % (in bottles) and 53 % (of somtum ingredients) of different types, concentrations, for single or combined use. These preservatives analyzed by high performance liquid chromatography (HPLC) method did not comply with Thai Community Product Standards for traditional Thai nam-pla-ra. The estimated daily intake of sorbic and benzoic acid is below that of the ADIs (Acceptable Daily Intake) in all cases as the amounts were 0.11 - 3.25 % for benzoic acid and 0.00 - 0.01 % for sorbic acid. The sodium risk was estimated as 46.9 - 81.7 % affecting people aged 35 years old to the elderly (≥ 65 years) in pasteurized-bottles (81.7 %) and somtum ingredients (70.3 %). The pathogenic and sanitary indicators of microbes in nam-pla-ra obtained from somtum vendors need to be improved by educating the somtum nam-pla-ra vendors in hygienic standards. The scientific data in this work can provide a proper guide to suitable amounts of intake leading to more effective government regulations for nam-pla-ra or related products. HIGHLIGHTS Synthetic preservatives and sodium critically assessed, and risks identified 70 % of products not per Thai Community Product Standards and 7 % not per FDA regulations Thai population not at risk of exceeding ADIs for preservative and sodium intake 6 % of various nam-pla-ra brands (54) had no/incorrect preservative declaration aureus, E. coli, C. perfringens, Salmonella spp. over standard (street vendors) GRAPHICAL ABSTRACT